Declined adipogenic potential of senescent MSCs due to shift in insulin signaling and altered exosome cargo - Voynova, Elizaveta; Kulebyakin, Konstantin; Grigorieva, Olga; Novoseletskaya, Ekaterina; Basalova, Natalia; Alexandrushkina, Natalia; Arbatskiy, Mikhail; Vigovskiy, Maxim; Sorokina, Anna; Zinoveva, Anna; Bakhchinyan, Elizaveta; Kalinina, Natalia; et al. (Frontiers in Cell and Developmental Biology, 2022)
Multipotent mesenchymal stromal cells (MSCs) maintain cellular homeostasis and regulate tissue renewal and repair both by differentiating into mesodermal lineage, e.g. adipocytes, or managing the functions of differentiated cells. Insulin is a key physiological inducer of MSC differentiation into adipocytes, and disturbances in MSC insulin sensitivity could negatively affect adipose tissue renewal. During aging, regulation and renewal of adipose tissue cells may be disrupted due to the altered insulin signaling and differentiation potential of senescent MSCs, promoting the development of serious metabolic diseases, including metabolic syndrome and obesity. However, the potential mechanisms mediating the dysfunction of adipose-derived senescent MSC remains unclear. We explored whether aging could affect the adipogenic potential of human adipose tissue-derived MSCs regulated by insulin. Age-associated senescent MSCs (isolated from donors older than 65 years) and MSCs in replicative senescence (long-term culture) were treated by insulin to induce adipogenic differentiation, and the efficiency of the process was compared to MSCs from young donors. Insulin-dependent signaling pathways were explored in these cells. We also analyzed the involvement of extracellular vesicles secreted by MSCs (MSC-EVs) into the regulation of adipogenic differentiation and insulin signaling of control and senescent cells. Also the microRNA profiles of MSC-EVs from aged and young donors were compared using targeted PCR arrays. Both replicatively and chronologically senescent MSCs showed a noticeably decreased adipogenic potential. This was associated with insulin resistance of MSCs from aged donors caused by the increase in the basal level of activation of crucial insulin-dependent intracellular effectors ERK1/2 and Akt. To assess the impact of the paracrine cross-talk of MSCs, we analyzed microRNAs profile differences in MSC-EVs and revealed that senescent MSCs produced EVs with increased content of miRNAs targeting components of insulin-dependent signaling cascade PTEN, MAPK1, GAREM1 and some other targets. We also confirmed these data by differentiation of control MSCs in the presence of EVs from senescent cells and vice versa. Thus, aging attenuated the adipogenic potential of MSCs due to autocrine or paracrine-dependent induction of insulin resistance associated with the specific changes in MSC-EV cargo.